PF.14 Isolated Borderline Fetal Cerebral Ventriculomegaly – Role of Magnetic Resonance Imaging (MRI). (26th April 2013) - Gabriel, JW; Dworkin, R; To, M; Bower, S; Zosmer, N; Akeolar, R; Flack, N
Abstract : Objective: To examine the role of third trimester magnetic resonance imaging (MRI) in fetuses diagnosed with isolated borderline cerebral ventriculomegaly at the routine second trimester fetal anomaly scan. Methods: This was a retrospective cohort study of 159 fetuses with apparently isolated borderline ventriculomegaly (9–12 mm) diagnosed at the routine second trimester ultrasound scan at a median of 22 (range 19–24) weeks' gestation and no additional findings at a repeat scan 6–8 weeks later. Follow up cerebral MRI was carried out at 28–34 weeks and the number of cases in which this investigation demonstrated abnormal findings was calculated. The patients were examined in a tertiary fetal medicine unit between 2005 and 2012. Results: In 7 (4.4%) of the 159 cases the MRI scan demonstrated findings not seen by ultrasound. These included partial agenesis of the corpus callosum (n = 2), delayed sulcation disorders (n = 1), heterotopia (n = 2), germinal matrix haemorrhage (n = 1), and destruction of the septum pellucidum (n = 1). Conclusions: In about 4% of fetuses with apparently isolated borderline cerebral ventriculomegaly an MRI scan demonstrates potentially clinically significant pathological findings.